Critical Thinking for the Modern Muslim Woman Psychology Student: A Summer in Islamabad - Podur, Justin (Radical Teacher, 2015)
Teaching critical thinking at the International Islamic University - Islamabad (IIU-I) in 2008 gave me a chance to reflect on religion and politics, leftism and anti-imperialism, and to learn more about the region. Some reflections for radical teachers.